Uniminuto blockchain (Memorias Sifored - Encuentros Educación UAN, 2023)
The document addresses the issue of insecure and inefficient student transactions, typically conducted through cash payments or bank transfers. The proposal involves the implementation of a cryptocurrency backed by blockchain as a solution. This technology holds the promise of providing greater security and transparency in student transactions, thereby enhancing their university experience. Notably, the potential to establish a rewards system based on this cryptocurrency is highlighted, where students accrue points for academic achievements and participation, which could improve the institution's image. The document also outlines the methodology used, including the SCRUM approach for project management, and the technologies employed, such as HTML, CSS, PHP, and Docker. It provides an overview of the project implementation, encompassing communication with blockchain and the creation of a dashboard.
Keywords: Blockchain Technology; Cryptocurrencies; User Transactions; Middleware; Dashboard